Implementasi Cyber Public Relations pada Progresif Digital Media sebagai Media Internal Pondok Pesantren - Aqila Nur Rahmalia (Jurnal Nomosleca, 2023)
The era of communication and information technology advancement demands a revolution. Media Convergence requires PR Practitioners to innovate their communication strategy. This study uses a descriptive qualitative approach with a case study method that focuses on Progresif Digital Media. The results of the study show that Media Internal that founded by the Leaders of the Bumi Shalawat Islamic Boarding School as a modern daâ€™wah platform can be used as one of the Cyber-PR communication tools to provide information about the Organization to the Public.Â